OSTEOARTHRITIS - RISE OF AN UNRECOGNIZED EPIDEMIC - Pradhan, Anmol Basudev (Journal of Medical Genetics and Clinical Biology, 2024)
Osteoarthritis (OA) is a degenerative joint disease characterized by the breakdown of cartilage, leading to pain, stiffness, and reduced mobility. Despite being the most common form of arthritis, OA is often underrecognized and undertreated. This article explores the rise of OA, its prevalence in developed versus developing nations, and the multifaceted factors contributing to its increasing incidence. We delve into the relationship between OA and nutritional factors, the impact of genetically modified foods and pesticides, and advancements in treatment options. By examining the latest research, we aim to highlight the need for greater awareness and more effective management strategies for this growing public health concern